Evaluation of The Role of Transrectal Fine Needle Aspiration As A Diagnostic Modality in The Diseases of Prostate with Review of Literature - Khan, Ansar A; Jain, Prashant K; Juneja, Binjul; Talha, Mohammad; Mehdi, Ghazala; Akhtar, Kafil; YS, Ghahlaut (Annals of Pathology and Laboratory Medicine, 2019)
INTRODUCTION: Transrectal fine needle aspiration cytology is feasible, reliable and highly sensitive diagnostic tool for the diagnosis of prostatic diseases. It mostly involves the elderly men, whose population is increasing in our country with the demographic shift of longitude. AIMS AND OBJECTIVES: To evaluate the sensitivity, specificity and positive productive value of transrectal fine needle aspiration cytology in addition to other advantages so that it could be accepted as a primary screening tool in the selection of the patients for biopsy and treatment of prostatic lesions. MATERIAL AND METHODS: Transrectal FNAC was performed in 49 patients, in clinically diagnosed cases of prostate diseases. Histomorphology was also carried out. RESULTS: Satisfactory smears could be obtained in 93.9% cases on first aspiration. The diagnostic accuracy for inflammatory disease was highest (100.0%), followed by malignant (88.8%), and benign lesions (82.9%), with a positive predictive value of 100.0% for malignancy of the prostate. False positivity was seen in 2.09% and false negativity in 11.2% cases. CONCLUSIONS: Transrectal FNAC is an accurate, sensitive, highly specific procedure with a high positive predictive value with negligible complication with an additional advantage of possible assessment of prognosis.